Capacity and Entry Under Demand Uncertainty - Perrakis, Stylianos; Warskett, George (Review of Economic Studies, 1983)
This paper examines the decision to enter into a sector dominated by a monopoly if demand is random at entry time. Given a two-period world, the monopolist enters initially and enjoys an uncontested monopoly for one period, while the entrant may enter and compete during the second period. Demand is random one period earlier and independently distributed in both periods and entry corresponds to an irreversible capacity choice, made under certain demand. All other production decisions take place after demand has been revealed. Risk-neutrality is assumed on both sides. If entry occurs then there is a Cournot duopoly in the second period. It is shown that concurrently with this Cournot production game, there is a separate Stackelberg-type game with capacities as decision variables. Entry-deterrence conditions are derived under general demand and cost assumptions. It is shown that demand uncertainty changes several of the results of similar certain demand models.